Examining Schellenberg's Hiddenness Argument - Weidner, Veronika (Palgrave Frontiers in Philosophy of Religion, 2018)
This book examines the so-called hiddenness argument of the Canadian philosopher John L. Schellenberg. The hiddenness of God is a topic evincing a rich tradition in the monotheistic religions of Judaism, Christianity, and Islam. Rather recently, an argument emerged claiming that the hiddenness of God reveals on closer inspection the non-existence of God. Some say that Schellenberg ́s hiddenness argument is likely as forceful as the argument from evil rendering theism rather implausible or even false. In this book, an account of the traditional theistic notion of divine hiddenness is presented, which contrasts sharply from Schellenberg ́s use of the term. Moreover, a well-needed detailed exposition of the premises of the hiddenness argument is offered, thereby preparing the ground for an even more in-depth future hiddenness debate. Furthermore, a reply to the argument is given which challenges the truth of one specific subpremise, according to which belief that God exists is necessary in order to personally relate to God. Even though a plausible case is made that the hiddenness argument is unsound, it is beyond dispute that the argument deserves more serious reflection by theists and atheists alike. .